Environmental Attributes Review of Muara Angke Fish Market and Auction, Jakarta, Indonesia - Finta Lissimia; Gian Wahyu Riyadi; Rivan Bryan Tirta; Anisa Anisa (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
Environmental attributes as a design quality assessment material have been put forward since 1980. Muara Angke Fish Market and Auction is the largest fish auction facility in Indonesia. Its development has received attention from the community for a long time. This article intends to examine the quality of the Muara Angke design by using environmental attributes proposed by Weisman in 1980. The study was conducted by first determining the attributes to be used, namely activity, accessibility, and sociality. The research method is descriptive qualitative by examining these three aspects at Muara Angke Fish Market and Auction. Market facilities and fish auction in Muara Angke are considered feasible in terms of activities and sociality. However, accessibility needs to be improved. The combination of one-door access and linear circulation is suitable to reach all points, but the absence of distribution of circulation paths between sellers, buyers, and goods makes the main route congested, especially in the active phase of the market, namely at night.Keywords: Activity, Accessibility, Environmental Attributes, Muara Angke Fish Market and Auction, Sociality